2020
DOI: 10.3390/tropicalmed5040158
|View full text |Cite
|
Sign up to set email alerts
|

PrEP Use Awareness and Interest Cascade among MSM and Transgender Women Living in Bali, Indonesia

Abstract: Indonesia has not implemented HIV pre-exposure prophylaxis (PrEP) despite global calls for its scale-up, and there is limited information about attitudes towards PrEP among its potential users. We aim to present a PrEP cascade among men who have sex with men (MSM) and transgender women (known locally as “waria”) in Denpasar, Bali, from a cross-sectional survey with 220 HIV-negative MSM/waria recruited from one clinic in Denpasar. Only 16.4% of participants had heard of PrEP before. From first-to-last steps inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 23 publications
1
16
0
2
Order By: Relevance
“…We also found that only 2.6% of anal intercourse events were protected by PrEP in either the respondent or their partner. This supports similar findings of very low PrEP use among MSM/waria in Bali [5], and Indonesia more broadly [24]. Due to this lower use of PrEP, CLAI protected by biomedical prevention was still a minority practice in our study.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…We also found that only 2.6% of anal intercourse events were protected by PrEP in either the respondent or their partner. This supports similar findings of very low PrEP use among MSM/waria in Bali [5], and Indonesia more broadly [24]. Due to this lower use of PrEP, CLAI protected by biomedical prevention was still a minority practice in our study.…”
Section: Discussionsupporting
confidence: 91%
“…Finally, in bivariate analysis, the degree of social connection respondents had to other MSM/waria was associated with lower potential HIV transmission risk. Higher social engagement has been associated with condom use, HIV testing, and PrEP in international research [20][21][22], as well as with greater interest in using PrEP among MSM/waria in Bali [5].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations